TPACK Based Differentiated Problem Posing to Enhance Entrepreneurial Digital Problem Solving - Derlina, Derlina; Zuhra, Siti; Mihardi, Satria; Lubis, Rajo Hasim; Purba, John Tampil; Stephanie, Stephanie (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study aims to determine the effect of TPACK-based differentiated learning on high school students' problem-solving abilities and motivation. The study, conducted at Private Senior High School PAB 8 Saentis Sei Tuan, used a quasi-experiment method with two classes: the experimental class, which used the differentiated problem solving model based on TPACK, and the control class, which used the conventional school learning model without differentiation. The results of this study indicate that the average post-test score for student problem-solving abilities in the experimental class was higher than in the control class. Statistical testing using two-way ANOVA showed that the problem-solving skills of students taught with the TPACK-based differentiated learning model demonstrated a significant influence between the learning model and motivation on students' problem-solving skills, as well as an interaction between the TPACK based problem posing learning model and motivation in terms of problem-solving skills. These findings have practical implications for educators, providing evidence that the TPACK-based differentiated problem-posing learning model is more effective in improving students' problem solving abilities than the conventional learning model, with learning motivation also playing an essential role in enhancing student problem-solving skills.